Solid solutions of flexible host–guest supramolecules for tuning molecular motion and phase transitions. Issue 59 (2nd July 2021) - Zhou, Xun-Hui; Zeng, Ying; Tang, Shao-Bin; Yu, Zi-Ru; Cao, Li-Ming; Du, Zi-Yi; He, Chun-Ting
Abstract : By utilizing supramolecular complex as a deformable/elastic substitutional component, we put forward a unique strategy for the formation of molecular solid solutions, which can modulate the molecular motion and phase transition in molecular solids. Abstract : By utilizing a supramolecular complex rather than an individual molecule as a deformable and elastic substitutional component, we put forward a solid-solution strategy and demonstrate an example of how two related yet non-isostructural crystalline host–guest compounds can form molecular solid solutions. Interestingly, such a strategy can effectively and continuously modulate the molecular motion and phase transition in them, as revealed by the variable-temperature/frequency dielectric responses.